Say my name - Ho, Joanna (Harper, an imprint of HarperCollins Publishers, 2023)
"Say My Name is a meaningful tale about the power of names. They reveal our personal histories, weaving an intricate story of the past and connecting us to the future. Names -- and saying them correctly -- are important. Six captivating kids of Chinese, Tongan, Persian, Navajo, Mexican, and Ghanaian decent proudly celebrate their names, languages, and cultures. From Johanna Ho, New York Times bestselling author of Eyes That Kiss in the Corners, and acclaimed illustrator Khoa Lee comes this lyrical picture book with a powerful theme: saying and understanding our names is the only way we can truly know each other."--